Significance of Sex Differences in ncRNAs Expression and Function in Pregnancy and Related Complications - Rosaria Varì (MDPI AG, 2021)
In the era of personalized medicine, fetal sex-specific research is of utmost importance for comprehending the mechanisms governing pregnancy and pregnancy-related complications. In recent times, noncoding RNAs (ncRNAs) have gained increasing attention as critical players in gene regulation and disease pathogenesis, and as candidate biomarkers in human diseases as well. Different types of ncRNAs, including microRNAs (miRNAs), piwi-interacting RNAs (piRNAs), long noncoding RNAs (lncRNAs), and circular RNAs (circRNAs), participate in every step of pregnancy progression, although studies taking into consideration fetal sex as a central variable are still limited. To date, most of the available data have been obtained investigating sex-specific placental miRNA expression. Several studies revealed that miRNAs regulate the (patho)-physiological processes in a sexually dimorphic manner, ensuring normal fetal development, successful pregnancy, and susceptibility to diseases. Moreover, the observation that ncRNA profiles differ according to cells, tissues, and developmental stages of pregnancy, along with the complex interactions among different types of ncRNAs in regulating gene expression, strongly indicates that more studies are needed to understand the role of sex-specific ncRNA in pregnancy and associated disorders.